Pengembangan aplikasi “SIMBA” (Social studies instructional media based android) untuk mata pelajaran IPS kelas VII SMP - Neni Wahyuningtyas; M. Haris Yahya (University of Muhammadiyah Malang, 2021)
Media is an important component in multidisciplinary social studies learning that must be presented in an integrated method. This study aimed to design learning media